1985
DOI: 10.1111/j.1460-2695.1985.tb00416.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact Fatigue Crack Growth Behaviour of Metallic Materials

Abstract: The impact fatigue crack growth characteristics of a low carbon steel and an aluminium alloy were studied. An impact fatigue testing machine of the Hopkinson bar type was used in these experiments to conduct a series of crack growth tests under simple impact stresses.The following characteristics of impact fatigue crack growth behaviour were revealed: (1) crack growth rate is higher in impact fatigue than in non-impact fatigue; (2) crack opening ratio in impact fatigue takes a higher value than in non-impact f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Some studies on IF tried to verify the applicability of Paris law for IF and to determine the values of the material constants C and m in this case (Dumitru et al 2006;Iguchi et al 1979;Nakayama and Tanaka 1984;Tanaka et al 1985;Murakami and Akizono 1982;Kobayashi 2000). It should be mentioned that the variation of the stress intensity factor was calculated with the known solutions for static cases, in which the values of the load were considered the recorded ones during impact tests.…”
Section: Particularities Of Impact Fatigue Comparing With Non-impact mentioning
confidence: 99%
“…Some studies on IF tried to verify the applicability of Paris law for IF and to determine the values of the material constants C and m in this case (Dumitru et al 2006;Iguchi et al 1979;Nakayama and Tanaka 1984;Tanaka et al 1985;Murakami and Akizono 1982;Kobayashi 2000). It should be mentioned that the variation of the stress intensity factor was calculated with the known solutions for static cases, in which the values of the load were considered the recorded ones during impact tests.…”
Section: Particularities Of Impact Fatigue Comparing With Non-impact mentioning
confidence: 99%
“…
The authors' previous studies on the crack growth under impact fatigue load for several metallic materials have revealed that the crack growth rate da/dN is higher in impact fatigue than in non-impact fatigue when compared on a da/dN-AK diagram and, in some cases, da/dN in impact fatigue shows its dependence on an applied stress range; the larger the applied stress range the higher the value of da/dN [1][2][3][4][5].Such features of impact fatigue crack growth suggest that the development of plasticity near the crack tip in impact fatigue is different from that in non-impact fatigue.In this study, microscopic deformation characteristics of material in the area including a crack propagated under impact load were observed by using fine meshes produced on a specimen surface by means of fine grating technique [6]. A discussion was made on the observed result by comparing it with the result obtained under non-impact load.

High strength low alloy steel HT-60 supplied as was used in the experiment, whose ultimate tensile MPa.

The specimen was center notched plate with a the width of 30mm.

Impact fatigue tests were conducted by using an machine of Hopkinson bar type at a loading rate of shows an example of impact stress pattern obtained 3.2 mm thick plates strength is about 600 thickness of 2mm and impact fatigue testing 9Hz [4,5].

Figure 1 by this testing machine.

…”
mentioning
confidence: 99%
“…A discussion was made on the observed result by comparing it with the result obtained under non-impact load.High strength low alloy steel HT-60 supplied as was used in the experiment, whose ultimate tensile MPa.The specimen was center notched plate with a the width of 30mm.Impact fatigue tests were conducted by using an machine of Hopkinson bar type at a loading rate of shows an example of impact stress pattern obtained 3.2 mm thick plates strength is about 600 thickness of 2mm and impact fatigue testing 9Hz [4,5].Figure 1 by this testing machine. Crack growth tests in non-impact fatigue were made by an electro-hydraulic servo type fatigue testing machine at a loading rate of 30Hz, and stress ratio R was chosen as zero to coincide with the impact stress pattern shown in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations